Presentación atípica del síndrome de Gorham-Stout. Caso clínico - González Luna, Alejandro (2015)
Gorham-Stout syndrome is an extremely rare pathology, of unknown etiology. It is characterized by proliferation of vascular channels that causes destruction and reabsorption of the bone matrix. We present a nine year-old male patient with an acute episode characterized by fever, chest pain, respiratory distress and dyspnea. The patient was submitted to computed tomography scan and a biopsy. The findings in the biopsy were multiple lytic lesions, osteolysis, and a mediastinal lymphangioma (lymphangiomatosis). The diagnosis was Gorham-Stout syndrome with atypical presentation.